(untitled) (Nigerian Journal of Technology, 2017)
The effects of abattoir wastewater pollution at New Artisan River in New Artisan, Enugu East, Enugu State of Nigeria were investigated. The study involved the collection of water samples at the designated points from the New Artisan River where the abattoir wastewaters are discharged. The physical, chemical and bacteriological analyses of the wastewater samples were conducted using standard analytical methods. Results of the laboratory tests were analyzed using statistical tests. The results obtained were compared with World Health Organization (WHO) and other international standards. The results obtained were pH; 6.54 at 25.0oC, biochemical oxygen demand (BOD); 5009(mg/L),chemical oxygen demand (COD); 3820(mg/L), total suspended solids (TSS); 97.3(mg/L) , total dissolved solids (TDS); 56.7(mg/L) , conductivity; 113(µS/cm) , , dissolved oxygen (DO); 8.60(mg/L) , turbidity; 24.0(NTU), colour; 117(Pt-Co), total solids (TS); 154(mg/L), total hardness (TH); 42.0(mg/L), calcium; 10.4(mg/L), coliforms; 9000(cfu/ml) and E-coli; 7500(cfu/ml) . Analyses of the results showed that the samples were highly polluted. Hence, appropriate measures are herein suggested as a means to control pollution discharge in New-Artisan River in order to enhance the quality of human and aquatic life http://dx.doi.org/10.4314/njt.v37i1.34